Observations of Gravity Wave Refraction and Its Causes and Consequences - Geldenhuys, Markus; Kaifler, Bernd; Preusse, Peter; Ungermann, J.; Alexander, Peter; Krasauskas, Lukas; Rhode, Sebastian; Woiwode, W.; Ern, M.; Rapp, Markus; Riese, M. (Journal of Geophysical Research: Atmospheres, 2023)
Horizontal gravity wave (GW) refraction was observed around the Andes and Drake Passage during the SouthTRAC campaign. GWs interact with the background wind through refraction and dissipation. This interaction helps to drive midatmospheric circulations and slows down the polar vortex by taking GW momentum flux (GWMF) from one location to another. The SouthTRAC campaign was composed to gain improved understanding of the propagation and dissipation of GWs. This study uses observational data from this campaign collected by the German High Altitude Long Range research aircraft on 12 September 2019. During the campaign a minor sudden stratospheric warming in the southern hemisphere occurred, which heavily influenced GW propagation and refraction and thus also the location and amount of GWMF deposition. Observations include measurements from below the aircraft by Gimballed Limb Observer for Radiance Imaging of the Atmosphere and above the aircraft by Airborne Lidar for the Middle Atmosphere. Refraction is identified in two different GW packets as low as ≈4 km and as high as 58 km. One GW packet of orographic origin and one of nonorographic origin is used to investigate refraction. Observations are supplemented by the Gravity-wave Regional Or Global Ray Tracer, a simplified mountain wave model, ERA5 data and high-resolution (3 km) WRF data. Contrary to some previous studies we find that refraction makes a noteworthy contribution in the amount and the location of GWMF deposition. This case study highlights the importance of refraction and provides compelling arguments that models should account for this.